Personal Data Protection for Victims of Sexual Violence in the Publication of Indonesian Cinematic Works - Rahmah, Auliyatur; Reny, Elsy; Rahmi, Nailur; Nurhikma (Al Ushuliy: Jurnal Mahasiswa Syariah dan Hukum, 2025)
This research examines how the personal data of victims of sexual violence are protected in the publication of Indonesian film art. It aims to explore the legal dynamics governing this issue from two perspectives: Indonesian legislation and the principles of siyasah dusturiyah. The study employs a normative juridical method with a statutory approach. To obtain relevant data, the researcher refers to primary legal sources, including the Qur’an, Hadith related to personal data protection, Law No. 33 of 2009 on Film, Law No. 27 of 2022 on Personal Data Protection (PDP), Law No. 12 of 2022 on Sexual Violence Crimes (TPKS), and Law No. 1 of 2024 on Electronic Information Transactions (ITE). Secondary sources include books and scholarly works that support the analysis. The findings reveal two key points. First, under the principle of lex specialis derogat legi generali, victims of sexual violence retain their rights as guaranteed in Article 69(d) of Law No. 12 of 2022 on Sexual Violence Crimes, including the protection of their identity and confidentiality. Films depicting sexual violence remain prohibited from presenting content that highlights pornography, as stated in Article 6(b) of Law No. 33 of 2009 on Film. Second, within the framework of fiqh siyasah dusturiyah, potential injustices are addressed through the establishment of a state institution known as sulṭah tashrī‘iyyah, which is responsible for formulating laws to be implemented in accordance with Allah’s provisions in Islamic sharia. One such principle is the prohibition against disseminating personal data through film media, as this protection aligns with the preservation of honor (ḥifẓ al-‘irḍ), one of the essential objectives (maqāṣid al-sharī‘ah) aimed at preventing human exploitation. Even when the victim’s family grants consent for the use of personal data in film production with good intentions, safeguarding a person’s dignity—whether the person is alive or deceased—remains a fundamental duty that must be upheld.